Effectiveness of proactive telephone counselling for smoking cessation in parents: Study protocol of a randomized controlled trial - Bricker Jonathan B; Kleinjan Marloes; Otten Roy; Schuck Kathrin; Engels Rutger CME (BMC, 2011)
Abstract Background Smoking is the world's fourth most common risk factor for disease, the leading preventable cause of death, and it is associated with tremendous social costs. In the Netherlands, the smoking prevalence rate is high. A total of 27.7% of the population over age 15 years smokes. In addition to the direct advantages of smoking cessation for the smoker, parents who quit smoking may also decrease their children's risk of smoking initiation. Methods/Design A randomized controlled trial will be conducted to evaluate the effectiveness of proactive telephone counselling to increase smoking cessation rates among smoking parents. A total of 512 smoking parents will be proactively recruited through their children's primary schools and randomly assigned to either proactive telephone counselling or a control condition. Proactive telephone counselling will consist of up to seven counsellor-initiated telephone calls (based on cognitive-behavioural skill building and Motivational Interviewing), distributed over a period of three months. Three supplementary brochures will also be provided. In the control condition, parents will receive a standard brochure to aid smoking cessation. Assessments will take place at baseline, three months after start of the intervention (post-measurement), and twelve months after start of the intervention (follow-up measurement). Primary outcome measures will include sustained abstinence between post-measurement and follow-up measurement and 7-day point prevalence abstinence and 24-hours point prevalence abstinence at both post- and follow-up measurement. Several secondary outcome measures will also be included (e.g., smoking intensity, smoking policies at home). In addition, we will evaluate smoking-related cognitions (e.g., attitudes towards smoking, social norms, self-efficacy, intention to smoke) in 9-12 year old children of smoking parents. Discussion This study protocol describes the design of a randomized controlled trial to evaluate the effectiveness of proactive telephone counselling in smoking cessation. It is expected that, in the telephone counseling condition, parental smoking cessation rates will be higher and children's cognitions will be less favorable about smoking compared to the control condition. Trial registration The protocol for this study is registered with the Netherlands Trial Register NTR2707.